‘Killing Me Softly With His/Her Song’: How Leaders Dismantle Followers’ Sense of Work Meaningfulness - Kipfelsberger, Petra; Kark, Ronit (Frontiers in Psychology, 2018)
Leaders influence followers’ meaning and play a key role in shaping their employees’ experience of work meaningfulness. While the dominant perspective in theory and in empirical work focuses on the positive influence of leaders on followers’ work meaningfulness, our conceptual model explores conditions in which leaders may harm followers’ sense of meaning. We introduce six types of conditions, i.e. leaders’ personality traits, leaders’ behaviors, the relationship between leader and follower, followers’ attributions, followers’ characteristics, and job design under which leaders’ meaning making efforts might harm or ‘kill’ followers’ sense of work meaningfulness. Accordingly, we explore how these conditions may interact with leaders’ meaning making efforts to lower levels of followers’ sense of meaning, and in turn, lead to negative personal outcomes (i.e., cynicism, lower well-being, and disengagement), as well as negative organizational outcomes (i.e., corrosive organizational energy, higher turnover rates, and lower organizational productivity). By doing so, our research extends the current literature, enabling a more comprehensive understanding of leaders’ influence on followers’ work meaningfulness, while considering the dark side of meaning making.